The role of local cultural factors in the achievement of the sustainable development goals. (2nd November 2022) - Ordonez‐Ponce, Eduardo
Abstract: The sustainable development goals (SDGs) are the greatest agreement achieved among countries. However, international policies such as the SDGs usually forget to include local cultural factors that would enable their achievement. Culture and sustainability have been studied in several contexts; however, the role that local culture plays in achieving sustainability has not been fully explored. This research addresses that gap by focusing on the SDGs globally and according to countries' income, continent, and region of origin. Hypotheses are tested through regression models using Hofstede's six cultural dimensions at the country level and the countries' overall and partial SDG scores. Results highlight significant relationships between cultural dimensions and countries' SDG scores in general and for groups of countries, and between cultural predictors and SDGs. Overall, power distance and masculinity contribute negatively to sustainability, whereas individualism, uncertainty avoidance, long‐term orientation, and indulgence affect sustainability positively. However, results vary across regions and SDGs. This article contributes with recommendations for policy and decision‐makers to address local SDGs and manage the different cultural dimensions of countries toward the accomplishment of sustainability. Certainly not an easy task.